Microplastic Exposure by Razor Clam Recreational Harvester-Consumers Along a Sparsely Populated Coastline - Baechler, Britta R.; Granek, Elise F.; Mazzone, Scott J.; Nielsen-Pincus, Max; Brander, Susanne M. (Frontiers in Marine Science, 2020)
Microplastics (MPs) are anthropogenic contaminants found in coastal and marine environments worldwide. Pacific razor clams (Siliqua patula), important for local indigenous culture, economy, gastronomy and food security along the United States West Coast, are subjected to myriad environmental stressors including predation, storm events, disease, toxins, and MPs. This study aimed to determine MP burdens in Olympic Coast, Washington Pacific razor clams and estimate annual MP exposure of recreational razor clam harvester-consumers from eating this species. We quantified suspected MP burdens in Pacific razor clams collected from eight tribal, recreational, and commercial harvest areas on the Olympic Coast in April 2018. We administered questionnaires to 107 recreational razor clam harvesters during the same timeframe to determine consumption patterns, preparation styles, knowledge and concerns about MPs, and demographics. Razor clams containing suspected MPs, primarily microfibers, were found at all eight sites. Average suspected MP burden differed by sample type (whole = 6.75 ± 0.60, gut-tissue = 7.88 ± 0.71, non-gut tissue = 4.96 ± 0.56, and cleaned samples = 3.44 ± 0.25). FTIR analyses of a random subset of microfiber-type MPs in whole and cleaned clams indicated material types of polyethylene terephthalate, cellulose acetate, cellophane, polyester, nylon, and cellulose. The average number of razor clams consumed per meal by Olympic Coast recreational razor clam harvesters was 4.27 ± 0.27, which varied by gender and ethnicity, but not income or age. Harvesters ate 0–209 meals/year of razor clams (16.2% harvested but did not eat razor clams), and most respondents (88.3%) fully cleaned razor clams before consuming them. Annual suspected MP exposure for razor clam harvester-consumers was 60–3,070 for cleaned and 120–6,020 for whole clams. Our findings suggest Olympic Coast recreational razor clam harvester-consumers are exposed to low levels of MPs from eating razor clams. MP exposure can be reduced by roughly 50% if clams are cleaned before consumption. Our work serves as an important reference in the growing portfolio of Pacific Northwest microplastic research, to inform future MP attenuation recommendations and development of human health standards for this type of pollution.